Update on Patellar Instability - Severino,Nilson Roberto (2021)
Abstract Patellar instability is a multifactorial clinical condition that affects a significant number of patients and occurs due to morphological variations of the joint and patellofemoral alignment. The present literature review study aimed to identify and summarize current concepts on patellar instability, in relation to associated risk factors, diagnostic criteria, and the benefits and risks of conservative and surgical treatments. For this purpose, a search was conducted in the following electronic databases: MEDLINE (via Pubmed), LILACS and Cochrane Library. It is concluded that the accurate diagnosis depends on the detailed clinical evaluation, including the history and possible individual risk factors, as well as imaging exams. The initial treatment of patellar instability is still controversial, and requires the combination of conservative and surgical interventions, taking into consideration both soft tissues and bone structures, the latter being the most common reason for choosing surgical treatment, especially lateral patellar instability.